Diets, Fruit and Vegetable Intake and Nutritional Status in Tanzania: Scoping Review - Amunga, Dorcas; Hess, S.; Grant, F.; Kinabo, J.; Olney, Deanna K. (2024)
Globally, the intake of fruit and vegetables (F&V) is far below the recommended levels, contributing to various health challenges including micronutrient deficiencies and non‐communicable diseases. In Tanzania, where the triple burden of malnutrition persists, there is a need to identify gaps in evidence, better understand diets and F&V intake and identify promising interventions for improved intake. We conducted a scoping review to summarize the evidence on dietary intake, F&V intake and nutritional status in Tanzania. This included three separate literature searches in PubMed covering the years 2012–2023. A total of 62, 37 and 15 articles met predefined eligibility criteria for the review of overall diet, dietary intake of F&V and nutritional status, respectively. Identified studies suggest that overall dietary practices among all population groups were primarily based on carbohydrate‐rich foods, complementary feeding practices were suboptimal among young children and a low proportion of women of reproductive age (WRA) and pregnant and lactating women achieved minimum dietary diversity for women (MDD‐W). Across all population groups, F&V intake was below the recommended 400 g per day. Analysis of nutritional status in Tanzania in population representative surveys showed high stunting prevalence in children below 5 years of age, and a high prevalence of overweight and obesity among WRA, particularly in urban areas. Additional research is needed to understand better the complex interactions between diet and nutrition and health outcomes, and to identify efficient and cost‐effective strategies to improve overall dietary quality, including increasing F&V intake.